Thin-walled graphitic nanocages as a unique platform for amperometric glucose biosensor - Guo, Chun Xian (2011)
A thin-walled graphitic nanocages material with well-developed graphitic structure, large specific surface area and pronounced mesoporosity was synthesized and used to construct a sensing interface for an amperometric glucose biosensor, showing a high and reproducible sensitivity of 13.3 μA mM−1 cm−2, linear dynamic range of 0.02−6.2 mM, and fast response time of 5 s. It was successfully used to accurately detect glucose in human serum with effective discrimination to common interference species such as dopamine, ascorbic acid, acetaminophen, and uric acid.